Memory and identity in the learned world : community formation in the early modern world of learning and science - Scholten, Koen; Miert, Dirk van; Enenkel, K. A. E. (Intersections : interdisciplinary studies in early modern culture,, 2022)
"Memory and Identity in the Learned World offers a detailed and varied account of community formation in the early modern world of learning and science. The book traces how collective identity, institutional memory and modes of remembrance helped to shape learned and scientific communities. The case studies in this book analyse how learned communities and individuals presented and represented themselves, for example in letters, biographies, histories, journals, opera omnia, monuments, academic travels and memorials. By bringing together the perspectives of historians of literature, scholarship, universities, science, and art, this volume studies knowledge communities by looking at the centrality of collective identity and memory in their formations and reformations"--